Existency of Alu Katentong Arts in Padang Laweh - Fauziah Rahman; Syeilendra Syeilendra (Science and Environmental Journal for Postgraduate, 2021)
This study aims to determine the existence of Alu Katentong art in Padang Laweh Sub-district, Tanah Datar Regency. This type of research is qualitative research with the intention of understanding the phenomenon holistically. This study also uses a descriptive analysis method which intends to provide the variables under study in accordance with the actual situation. The object of this research is Alu Katentong art. The information obtained about the object of research is emphasized on the words and pictures which are carried out in stages. The instrument in this study is the researcher herself, equipped with supporting tools to support the completeness of the data obtained in the field. In this study, data collection was carried out through observation, interviews, documentation, and literature study. The data analysis used is by way of data reduction, data presentation, and drawing conclusions. The results showed that the art of Alu Katentong still exists today. The art of Alu Katentong can be seen in the procession of the wedding ceremony which is held at the residence of the bride. This art has its own charm because it is played by women using a Alu as the main instrument. In the Alu Katentong art performance there are elements of supporting the presentation, namely 1) players, 2) instruments, 3) songs, 4) costumes and make-up, 5) time and place of performance, 6) audiences.